Hepatitis C virus antibody titers associated with cognitive dysfunction in an asymptomatic community-based sample. Issue 8 (13th September 2016) - Ibrahim, Ibtihal; Salah, Hala; El Sayed, Hanan; Mansour, Hader; Eissa, Ahmed; Wood, Joel; Fathi, Warda; Tobar, Salwa; Gur, Ruben C.; Gur, Raquel E.; Dickerson, Faith; Yolken, Robert H; et al.
ABSTRACT: Background : Hepatitis C virus (HCV) infection is associated with cognitive dysfunction in clinic-based studies. The risk could be attributed to factors such as antiviral medications, substance abuse, or coincidental infection. Aim : The aim was to evaluate cognitive function in relation to HCV antibody titers in a community-based sample of asymptomatic individuals at low risk for substance abuse. Method : Adults were ascertained from a community in Mansoura, Egypt, where HCV is endemic ( n = 258). Cognitive performance was evaluated using the Arabic version of the Penn Computerized Neurocognitive Battery. Substance abuse and psychopathology were also assessed. Antibodies to HCV and Toxoplasma gondii (TOX), a common protozoan that can affect cognition, were estimated using serological IgG assays. Results : The prevalence of HCV and TOX infection was 17.6% and 52.9%, respectively. HCV antibody titers were significantly associated with worse function in four cognitive tests for accuracy and three tests for speed, after adjusting for covariates ( p < .05, beta coefficients, 2.1–3.2). TOX antibody titers were associated with impaired accuracy in one test. Conclusions : The association between HCV antibody titers and cognitive impairment is not mediated by antiviral treatment or substance abuse in this sample. Whether HCV has a causal role in the cognitive dysfunction should be investigated.